CONCEPTS OF STUDY OF THE THEORY OF VIRTUALITY IN PEDAGOGICAL SCIENCE - Pavliuk, Roman O. (Educological discourse, 2014)
Modern concepts of the study of the theory of virtuality in the context of pedagogical sciences are determined. The basic outlooks of scientists and concepts regarding structure and characteristics of the theory of virtual reality are underlined. The basic ontological and methodological approaches to the study and research of theories of virtuality, virtuality and virtual reality are examined.